Outliers matter: correlation between S1 IgG SARS-CoV-2 antibodies and neutralizing SARS-CoV-2 antibodies - Hocher, Berthold; Schönbrunn, Anne; Chen, Xin; Krämer, Bernhard; Baehr, Volker von (Microorganisms, 2022)
Vaccination against the SARS-CoV-2 virus or infection with SARS-CoV-2 will lead to the development of IgG antibodies against the S1 protein of the SARS-CoV-2 virus. However, even despite having high levels of IgG antibodies against the S1 protein of the SARS-CoV-2 virus, (re-)infection may occur. We thus examined 2994 consecutive blood samples of outpatients from the Berlin-Brandenburg area in Germany in which IgG antibodies against the S1 protein of the SARS-CoV-2 virus as well as neutralizing SARS-CoV-2 virus antibodies were determined from the same sample. When analyzing the entire study population (2994 outpatients), we saw that S1 IgG antibodies (women: 223.98 ± 3.81; men: 207.80 ± 4.59; p = 0.014) and neutralizing antibodies (women: 66.65 ± 0.82; men: 62.88 ± 1.01; p = 0.021) are slightly higher in women than in men. Curve fitting revealed a good non-linear relationship between S1 IgG and neutralizing SARS-CoV-2 antibodies. However, 51 out of the 2994 blood samples from individual subjects were positive with regard to the neutralizing antibodies and at the same time negative for S1 IgG antibodies, and 112 out of the 2994 blood samples from individual subjects were negative with regard to the neutralizing antibodies and at the same time positive for S1 IgG antibodies. In conclusion, our study shows that there is a relevant number of patients who, despite developing significant titers of S1 antibodies, do not have relevant amounts of neutralizing antibody titers and are probably at high risk of (re-)infection.
Gesehen am 04.01.2023